Dragon Pearl - Lee, Yoon Ha 1979-; To, Vivienne (Los Angeles ; Disney-Hyperion, 2019)
Min, a thirteen-year-old girl with fox-magic, stows away on a battle cruiser and impersonates a cadet in order to solve the mystery of what happened to her older brother in the Thousand World Space Forces.
Keywords: Magic -- Juvenile fiction; Impersonation -- Juvenile fiction; Shape-shifting -- Juvenile fiction; Stowaways -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Space flight -- Juvenile fiction; Adventure stories; Magic -- Fiction; Impersonation -- Fiction; Shape-shifting -- Fiction; Stowaways -- Fiction; Brothers and sisters -- Fiction; Space flight -- Fiction; Adventure and adventurers -- Fiction; Science fiction; Action and adventure fiction; Space operas